Patrimonial Imaginaries and Ethnographic Practice: Cultural Management Experiences in the Southwest of Bueno Aires Province, Argentina - Iparraguirre, Gonzalo (Revista de Antropología Social, 2014)
In the following article I present an ethnographic study of patrimonial imaginaries, cultural heritage management and its scientific-political implications in the southwest of the province of Buenos Aires, Argentina. From my personal experience as a technician in management and research of cultural heritage between 2006 and 2012, I analyze two case studies that will allow us to think about the anthropological practice, the heritage management by different actors, and the construction of scientific knowledge based on social imaginaries analysis. I also discuss the importance of the ethnographic practice and the diagnosis of different social imaginaries when it comes to study heritage within the local community, the political authority, and the scientific community. Finally, I will provide a general guideline to elaborate a model of social intervention.